Mortality of Calanus helgolandicus: Sources, differences between the sexes and consumptive and nonconsumptive processes. (27th April 2018) - Maud, Jacqueline L.; Hirst, Andrew G.; Atkinson, Angus; Lindeque, Penelope K.; McEvoy, Andrea J.
Abstract: While losses from mortality are as important as gains from reproduction in zooplankton population dynamics, the former are more challenging to quantify. We used two approaches to provide complementary insights into the mortality of a biomass‐dominant copepod, Calanus helgolandicus, at Station L4 in the English Channel. Using a neutral‐red staining method, we found that dead carcasses represented a mean of 9% of the C. helgolandicus copepodites sampled. The resulting nonconsumptive mortality rates are the first that have been derived for C. helgolandicus ; and estimates suggest a contribution of 0–54% (median of 4.4%) to the total mortality rate. Consumptive mortality (i.e., that due to removal by predation), dominated for most of the year and contributed a mean of 89% to total mortality. Nonconsumptive mortality increased during summer and winter, and was positively related to maximum wind speed during the preceding 72 h, indicating that extreme weather events may lead to increased mortality. Using the Vertical Life Table approach, mortality rates across the CV‐adult male stage pair were on average ∼ 2.5 times greater than those of CV‐adult females. Adult male consumptive mortality rates were ∼ 6 times greater than those for females; adult male nonconsumptive rates were twice those of females, suggesting that predation is of greater significance to male loss rates. Summer CV‐adult mortality rates were positively correlated to temperature, and to the abundance of predatory chaetognaths and siphonophores, suggesting that the gelatinous predator assemblage is the dominant agent for population control of late stage copepodites of C. helgolandicus at L4.